STUDY OF THE SOLUBILITY OF WO3 IN HCL SOLUTIONS AT 450°C - Khodorevskays L.I.; Tikhomirova V.I.; Postonova L.E. (My University, 1990)
Information on the conditions of transport of tungsten is very important for interpreting physicochemical conditions of formation of ore bodies. Chloride and oxychloride complexes of tungsten have received much attention because chloride is one of the basic anions of hydrothermal fluids. The following paper reports results on the solubility of WO3 in pure water and CHl solutions (0.001 to 0.1 m/kg) at 450°C and 200 to 1000 bars. Results show that an increase in the mHCl of low-density solutions can cause effective transport of tungsten in the gaseous phase. Such conditions can be realized through the process of heterogenization (boiling) of the hydrothermal fluids. Such a process results in the enrichment of the volatile phase in HCl.